Prywatne apokalipsy końca wieku. O "Powieści naturalnej" Georgiego Gospodinowa - Radomirova, Anelia (Załącznik Kulturoznawczy, 2023)
In this article, I discuss Natural Novel by contemporary Bulgarian writer, Georgi Gospodinov. I focus on the theme of ‘private apocalypse’. The metaphor illustrates the dimension of personal crisis experienced by the hero and narrator of the novel. ‘Private apocalypse’ refers to the existential burden born by modern man, the burden of creating oneself in a world without constant references and values. It is a phrase meant to capture symbolically modern man’s homelessness and abandonment.